Clinical practice of the dental hygienist - Wilkins, Esther M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
From the Publisher: The cornerstone text of almost every dental hygienists library is now in its thoroughly updated Tenth Edition. Written in a straightforward, concise outline format, this text equips both students and practitioners with the clinical and educational skills needed for successful practice. Features include full-color artwork and photographs, case-based exercises, procedure boxes, and ethics boxes. The Tenth Edition presents the latest technical advances and research findings and includes a new chapter on teeth whitening.
54: Patient who is homebound -- Homebound patients -- Dental hygiene care and instruction -- Unconscious patient -- Terminally ill patient -- Everyday ethics -- Factors to teach the patient -- Factors to teach the caregiver -- References -- Suggested readings -- 55: Patient with a physical impairment -- Spinal cord dysfunctions -- Spinal cord injury -- Myelomeningocele -- Cerebrovascular accident (stroke) -- Muscular dystrophies -- Myasthenia Gravis -- Multiple Sclerosis -- Cerebral Palsy -- Bell's Palsy -- Parkinson's disease -- Arthritis -- Scleroderma (progressive systemic sclerosis) -- Kidney disease -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 56: Patient with a sensory disability -- Americans with Disabilities Act -- Visual impairment -- Hearing impairment -- Everyday ethics -- Factors to teach the patient -- Reference -- Suggested readings -- 57: Family abuse and neglect -- Child maltreatment -- Elder maltreatment -- Intimate partner abuse and violence -- Documentation -- Reporting maltreatment -- Forensic dentistry -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 58: Patient with a seizure disorder -- Epileptic syndromes -- Clinical manifestations -- Treatment -- Oral findings -- Dental hygiene care plan -- Emergency care -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 59: Patient with a mental disability -- Mental retardation -- Down Syndrome -- Autistic spectrum disorder -- Dental hygiene care -- Everyday ethics -- Factors to teach the patient -- Factors to teach the caregiver -- References -- Suggested readings -- 60: Patient with psychiatric disorder -- Schizophrenia -- Mood disorders -- Major depressive disorder -- Bipolar disorder -- Postpartum mood disturbances -- Anxiety disorders -- Eating disorders -- Anorexia Nervosa -- Bulimia Nervosa -- Psychiatric emergencies -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 61: Patient with a substance-related disorder -- Alcohol-related disorders -- Metabolism of alcohol -- Health hazards -- Fetal Alcohol Syndrome (FAS) -- Alcohol withdrawal syndrome -- Treatment for alcoholism -- Prescription and street drugs -- Most common drugs of abuse -- Treatment methods -- Dental hygiene care -- Clinical examination -- Clinical treatment and instruction -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 62: Patient with a respiratory disease -- Respiratory system -- Upper respiratory tract diseases -- Lower respiratory tract diseases -- Pneumonia -- Tuberculosis (TB) -- Asthma -- Chronic Obstructive Pulmonary Disease (COPD) -- Cystic Fibrosis -- Summary guidelines for dental hygiene care -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 63: Patient with a cardiovascular disease -- Classification -- Congenital heart diseases -- Rheumatic heart disease -- Mitral valve prolapse -- Infective endocarditis -- Hypertension -- Hypertensive heart disease -- Ischemic heart disease -- Angina pectoris -- Myocardial infarction -- Congestive heart failure -- Basic noninvasive treatment -- Surgical treatment -- Anticoagulant therapy -- Cardiac surgery -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 64: Patient with a blood disorder -- Oral findings suggestive of blood disorders -- Normal blood -- Anemias -- Iron deficiency anemia -- Megaloblastic anemias -- Sickle cell disease -- Polycythemias -- White blood cells -- Bleeding disorders -- Coagulation disorders -- Miscellaneous treatment suggestions for dental professionals -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- 65: Patient with diabetes mellitus -- Diabetes mellitus -- Insulin -- Diabetes mellitus etiologic classification -- Diagnosis of diabetes -- Complications of diabetes -- Medical treatment and modifications for diabetes control -- Medications -- Pancreas transplantation -- Blood glucose testing -- Oral relationships -- Dental hygiene care plan -- Everyday ethics -- Factors to teach the patient -- Diabetes insipidus -- References -- Suggested readings -- 66: Emergency care -- Prevention of emergencies -- Patient assessment -- Stress minimization -- Emergency materials and preparation -- Basic life support -- Rescue breathing -- External chest compressions -- Airway obstruction -- Oxygen administration -- Specific emergencies -- Everyday ethics -- Factors to teach the patient -- References -- Suggested readings -- Prefixes, suffixes, and combining forms -- Appendix 1: American Dental Hygienists' Association code of ethics for dental hygienists -- Appendix 2: Canadian Dental Hygienists' Association code of ethics -- Appendix 3: International Federation of Dental Hygienists' code of ethics -- Appendix 4: Guidelines for infection control in dental health-care settings 2003 -- Appendix 5: Average measurements of human teeth -- Index.
Includes bibliographical references and index.
Keywords: Dental hygiene; Dental Prophylaxis -- Outlines; Dental Hygienists -- Outlines